STRATEGI PENGEMBANGAN SMA SWASTA ISLAM UNTUK PENINGKATAN KOMPETENSI GLOBAL - Rosidin, Rosidin; Sugiyo; Hasyim, Ahmad Dardiri; Zuhri (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
The existence of Islamic private high schools (SMA) founded on foundations is constantly threatened by both public schools and the advancement of globalization currents. With such a big problem, private educational institutions must try to discover ways to survive and adapt accordingly in order to continue to exist. The method for reacting to these issues for private schools is unique, and it should be explored thoroughly so that it can serve as a model for other educational institutions. The study used qualitative methods and focused on five foundation-based Islamic private high schools in Demak, Central Java. Data is collected by observation, interviews, and documentation studies. Data analysis using interactive models, including data reduction, data submission, and conclusions. According to the study's findings, (1) foundation-based Islamic private schools (SMA) employ a variety of strategies, including traditional strategies, modern strategies, and comprehensive student networks, such as free transportation and recruitment of outstanding students (academic, non-academic, and cultural arts achievements). (2) Demak private schools use marketing mix methods such as superior pricing, diverse products, market focus, long-term promotional activities, and online school programs.